Innovations in Teaching 1969-70. Thirteen Projects of the Hilroy Fellowship Program - Canadian Teachers' Federation, Ottawa (Ontario).; Canadian Teachers' Federation, Ottawa (Ontario). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This document contains descriptions of 13 projects undertaker through the Hilroy Fellowship Program in Canada in 1969-70. The stated aim of the program is to encourage and reward classroom teachers who are developing new ideas for the improvement of teaching practices. Each project description contains the following information: (1) the name and address of the teacher; (2) the name and address of the school; (3) a review of the project including the title, purpose, age, and significant characteristics of the pupils, procedures followed, modifications, source or resource materials, and evaluation procedures used; and (4) general comments about the project. Many of the projects have in common an emphasis on individualized learning, field trips, student-initiated work and discussion, and the provision of enriching experiences for disadvantaged students. The projects deal with some of the following areas: pollution and conservation, language development in a culturally deprived area, science education, Canadian history, film,and drama. (CD)
ERIC Note: One abstract in French; For related documents, see SP 009 929-934.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Aids; Disadvantaged Youth; Discussion (Teaching Technique); Field Trips; Film Production; Individualized Instruction; Instructional Innovation; Language Arts; Reading Instruction; Student Improvement; Canada; Reports, Descriptive